Assessment of Olfactory Fossa Depth based on Keros Classification using Computerised tomography (Ct) in Age Groups of Both Genders - Mubina Lakhani; Iffat Raza; Rosheena Nabeel Khan; Maria Mohiuddin; Naushin Adnan; Nuzhat Hassan (Journal of Rawalpindi Medical College, 2022)
Objective: Keros classification based assessment of olfactory fossa depth in different age groups of both genders using computerized tomography (CT)